Exploring the track of Forensic Serology: A 23-Year Bibliometric Analysis - Pujari, Avinash J. (The Ukrainian Scientific Medical Youth Journal, 2025)
this bibliometric evaluation reviewed forensic serology studies from 2000 to 2023, utilising Scopus records to song guide trends, key contributors, and impactful research. The subject showed significant growth, with 201 documents posted at a four.89% annual boom price. Major members consist of Virginia Commonwealth University and fantastic researchers like Hanson EK and Juusola J. The studies highlight diverse file kinds and influential papers, emphasizing ongoing advancements and the want for global collaboration. Limitations encompass reliance on Scopus and ability language bias. Overall, the study demonstrates the dynamic progress in forensic serology and the significance of continued research.